Analysis of Primary Metabolites Content in Ketapang Seed Tempe (Terminalia Catappa) - Siska D. Wulandari; Siti Nuryanti; Tahril Tahril; Sitti Aminah (Universitas Tadulako, 2026)
Ketapang seed tempeh (Terminalia catappa) is made from ketapang seed waste through a fermentation process using Rhizopus sp., as with soybean tempeh. This study used a quantitative descriptive method to determine the content of primary metabolites, including fat, protein, and carbohydrates. Laboratory analysis was conducted at the Chemistry Education Laboratory, Tadulako University, using the Soxhlet method for fat, the Kjeldahl method for protein, and the phenol-sulfur method for carbohydrates, as well as organoleptic tests by 15 panellists. The results showed that ketapang seed tempeh had very low fat content (0.1714%), low protein (0.0189 g per 100 g sample), and moderate carbohydrate (10.06%). Fried ketapang tempeh was preferred by the panellists, although its acceptance level was still lower than that of soybean tempeh. The novelty of this study lies in the quantitative evaluation of primary metabolites in tempeh made entirely from ketapang seeds, which has not been previously reported. These findings indicate that ketapang seeds have the potential to serve as an alternative ingredient in the production of low-fat tempeh.